THE EFFECT OF PACKAGING TYPE AND STORAGE TEMPERATURE ON THE SHORT TERM STABILITY OF ELECTROLYTIC CONDUCTIVITY REFERENCE MATERIALS - AYU HINDAYANI; OMAN ZUAS; NURYATINI HAMIM (Journal of Engineering Studies and Research, 2021)
In this work, monitoring the effect of packaging type and storage temperature on the short term stability of calibration standard solution KCl 1 M were conducted. The KCl 1M were packaged in two types of packaging i.e., high-density polyethylene (HDPE) and glass bottle. The effects of packaging type and storage temperature were monitored for four weeks at 25 °C and 40 °C. The conductivity values of KCl 1 M in the HDPE and glass bottle were 111.61 mS/cm and 111.62 mS/cm, respectively. The results indicated that the KCl 1M solution at 25 °C in both HDPE and glass bottle were found to be good in short term stability and there was no significant different between the two packaging types. At temperature of 40 °C, however, short term stability of the KCl 1 M in a glass bottle was better than the HDPE bottle.